Menimbang Nasib Perempuan dalam Agama & Feminisme - Rofiq, Aunur (el Harakah: Jurnal Budaya Islam, 2001)
The inhuman treatment of others, however, can not be tolerated. The acts of violence, sexual harassment, and injustice against women prevailing throughout the period are no longer compatible with human rights, and the demands of the development of the level of consciousness, the education that no longer recognize the gender limit, even the religion of Allah that is revealed for the freedom of human beings from the shackles of the fitrah. This paper deals with the treatment of violence against women by discussing it through various perspectives. Why violence against women can happen, what is the factor behind it? Many factors or motives behind the violence. Cultural, social, political, ideological, racial, ethnic, religious, and even gender biased factors can trigger violence. The efforts of women's liberation by Indonesian feminists, can be said to be very noble. Even so religious social and cultural factors need to be considered. However, the feminism of the West is a role model, not free from the content of sociological value, culture, ideology, philosophy born there. Thus it is not wise, if Indonesian feminism uses the paradigm, or ideology of Western femme in offering the best solution for women of the Eastern nations-especially Indonesia. Perlakuan tidak manusiawi terhadap sesama, bagaimanapun tidak bisa dibiarkan. Tindak kekerasan, pelecehan seksual, dan ketidakadilan terhadap perempuan yang berlaku sepanjang kurun tidak lagi sesuai dengan HAM, dan tuntutan perkembangan tingkat kesadaran, pendidikan yang tidak lagi mengenal batas gender, bahkan agama Allah Swt yang diturunkan demi kebebasan manusia dari berbagai belenggu yang memasung fitrah. Tulisan ini mengangkat tentang perlakuan kekerasan pada perempuan dengan membahasnya melalui beragam perspektif. Mengapa kekerasan terhadap perempuan bisa terjadi, apa faktor di balik itu? Banyak faktor atau motif yang melatarbelakangi terjadinya kekerasan. Faktor budaya, sosial, politik, ideologi, ras, etnis, agama, bahkan pandangan bias gender bisa menjadi pemicu timbulnya kekerasan. Upaya pembebasan perempuan yang dilakukan para feminis Indonesia, bisa dikatakan sangat mulia. Sungguhpun begitu faktor sosial budaya timur yang religius perlu dipertimbangkan. Bagaimanapun lahimya feminisme Barat yang menjadi panutan, tidak bebas dari muatan nilai sosiologis, budaya, ideologi, filsafat yang lahir di sana. Dengan demikian tidaklah bijak, jika feminisme Indonesia menggunakan paradigma, atau ideologi femnisme Barat dalam menawarkan solusi terbaik untuk perempuan bangsa-bangsa Timur-khususnya Indonesia.